Impact of TeO2-B2O3 manipulation on optical and radiation shielding properties of mixed glass former borotellurite glass - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2023)
Impact of TeO2-B2O3 manipulation on optical and radiation shielding properties of mixed glass former borotellurite glass by Muhammad Noorazlan Abd Azis